A FORMULASI BISKUIT DENGAN TEPUNG IKAN TERI DAN ISOLATE PROTEIN KEDELAI (Glycine mix) (Stolephorus sp) SEBAGAI PMT-P UNTUK BALITA GIZI KURANG - Diah Ratnasari; Anggray Duvita Wahyani (Jurnal GIZIDO, 2021)
The use of anchovy flour and soy protein isolate to be processed into biscuits has the potential to be an appropriate PMT Supplementary Feeding for undernourished toddlers than biscuits on the market. This study aims to determine the effect of substitution of anchovy flour and soy protein isolate on the nutritional content and acceptability of PMT-P biscuits. This research is a complete experimental design, namely anchovy flour biscuits with soy protein isolate. This research is included in the field of food technology and society. The method used in this study used an experimental method with one factor being tried, namely the proportion of wheat flour compared to anchovy flour and soybean protein isolate consisting of 5 levels, namely: P1 = 100% : 0%; P2 = 80% : 20%; P3 = 60% : 40%; P4 = 40% : 60%; P5 = 20% : 80%. The experimental design used in this study was a completely randomized design. Each treatment was repeated 3 times to obtain 15 experimental units. The results of the calcium content in biscuits are known by laboratory tests, and acceptability will be carried out by hedonic test (preferred level) while statistical analysis by Analysis of Variance (ANOVA) test with 95% confidence level. The results showed that the highest average Calcium (Ca) content is P4 (formula 4) which is 1.32 mg Calcium content. The results of the ANOVA test are known to be p < 0.05 so that it can be concluded that there are differences in the content of Calcium in each treatment and preference test in the research that has been carried out and the analysis of color, texture, taste, aroma can be well received by consumers.